Stripping and VP Ellipsis in Reduced Temporal Adverbs. (26th August 2021) - Overfelt, Jason
Abstract: The first goal of this article is to argue that phrasal temporal adverbial constructions like Al left before Pat are derived via ellipsis from an underlying clausal source. The second goal is to demonstrate and account for the restricted distribution and interpretation of these reduced phrasal temporal adverbial constructions relative to their clausal counterparts and to temporal adverbial constructions targeted by VP ellipsis. The proposed analysis provides evidence for an operator–variable parallelism condition on ellipsis and supports models for an identity condition on ellipsis that allow the identification of an antecedent within the phrase‐structure representation of the utterance.